Incidence of thyroid disease in patients with forefoot deformity. Issue 4 (June 2020) - Tran, Sterling K.; Carr, James B.; Hall, Matthew J.; Park, Joseph S.; Cooper, Minton T.
Highlights: Thyroid disease is significantly associated with hallux valgus and lesser toe deformities. Thyroid disease present in 21.1% of studied foot and ankle clinic patients. National data confirms high incidence of thyroid disease in patients with forefoot disorders. Screening patients with forefoot disorders for thyroid disease is a reasonable application. Abstract: Background: Hallux valgus and lesser toe deformities are common foot disorders with substantial functional consequences. While the exact etiologies are multi-factorial, it is unknown if certain endocrine abnormalities, such as thyroid dysfunction, may be associated with these pathologies. The current study sought to investigate the prevalence of thyroid disease in patients with hallux valgus or lesser toe deformities. Methods: Every new patient who presented to our institution's foot and ankle clinic during a three-month time period was given a survey to determine the presence of a known thyroid disorder. The diagnosis for each visit was then recorded. Additionally, a national, publicly available database was queried for patients diagnosed with thyroid disease and concomitant hallux valgus or specific forefoot pathology. Odds ratios for the presence of thyroid dysfunction were then calculated for each patient group. Results: Three-hundred and fifty initial visit patient surveys were collected, and 74 (21.1%) patients had a known diagnosis of thyroid disease. The most common diagnoses were primary hypothyroidism (n = 61, 17.4%), secondary hypothyroidism (n = 6, 1.7%), thyroiditis (n = 4, 1.1%), and hyperthyroidism (n = 3, 0.9%). Thyroid disease was present in 16 of 26 patients (61.5%) with a diagnosis of hallux valgus (OR 7.3, CI[3.16–16.99], p < 0.0001 ). Lesser toe deformities, including hammertoes, mallet toes, bunionettes and crossover toes, were also significantly associated with thyroid disease (OR 5.45, CI[1.83–16.26], p < 0.002 ). The national database revealed 905, 924 patients with a diagnosis of a specific forefoot deformity, and 321, 656 of these patients (35.5%) had a concomitant diagnosis of a thyroid condition (OR 2.11, CI[2.10–2.12], p < 0.0001 ). Conclusions: The current study suggests a significant association between forefoot pathology and thyroid dysfunction, especially hallux valgus and lesser toe deformities. Increased understanding of these correlations may offer an important opportunity in population health management, both in diagnosis and treatment. While further studies with long-term outcomes are necessary, the early diagnosis of thyroid disease may provide an opportunity to predict and potentially alter the course of forefoot pathology.